2020
DOI: 10.1186/s13054-020-03385-5
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular-arterial uncoupling independently predicts survival in COVID-19 ARDS

Abstract: Aim To investigate the prevalence and prognostic impact of right heart failure and right ventricular-arterial uncoupling in Corona Virus Infectious Disease 2019 (COVID-19) complicated by an Acute Respiratory Distress Syndrome (ARDS). Methods Ninety-four consecutive patients (mean age 64 years) admitted for acute respiratory failure on COVID-19 were enrolled. Coupling of right ventricular function to the pulmonary circulation was evaluated by a comprehensive trans-thoracic echocardiography with focus on the tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
123
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(133 citation statements)
references
References 29 publications
7
123
3
Order By: Relevance
“…(Stockenhuber et al, 2020;Wibowo et al, 2021) Multiple studies has found that RV strain and TAPSE were associated with higher severity and mortality. (Bursi et al, 2020;D'Alto et al, 2020;Lassen et al, 2020;Li et al, 2020;Liu et al, 2020;Sattarzadeh Badkoubeh et al, 2021;Stockenhuber et al, 2020) LV function is usually preserved or hyperdynamic in COVID-19 patients. (Moody et al, 2020) If affected, this may be secondary to RV volume and excess pressure due to ventricular interdependence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Stockenhuber et al, 2020;Wibowo et al, 2021) Multiple studies has found that RV strain and TAPSE were associated with higher severity and mortality. (Bursi et al, 2020;D'Alto et al, 2020;Lassen et al, 2020;Li et al, 2020;Liu et al, 2020;Sattarzadeh Badkoubeh et al, 2021;Stockenhuber et al, 2020) LV function is usually preserved or hyperdynamic in COVID-19 patients. (Moody et al, 2020) If affected, this may be secondary to RV volume and excess pressure due to ventricular interdependence.…”
Section: Discussionmentioning
confidence: 99%
“…(Raymond Pranata et al, 2020a) COVID-19 itself is associated with myocardial injury and impaired right ventricle (RV) strain, which are independent predictors of poor prognosis. (D'Alto et al, 2020;Wibowo et al, 2021) Meanwhile, left ventricle (LV) function is usually relatively unaffected in the majority of COVID-19 patients. (Moody et al, 2020) Acute cor pulmonale or right heart failure (RHF) is a J o u r n a l P r e -p r o o f long-established complication of ARDS, in relation to disease severity and ventilatory strategies associated with permissive hypercapnia and pulmonary hyperinflation.…”
Section: Prospero Id: Crd42021232194mentioning
confidence: 99%
See 1 more Smart Citation
“… 21 It remains however unclear whether RVD in the presence of myocardial complications without micro- or macrovascular pulmonary thrombosis is caused by RV ischemia, RV-PA uncoupling or severe inflammation. 23 …”
Section: Pathophysiology Of Rv Dysfunction In Covid-19mentioning
confidence: 99%
“…Hypoxemia and/or hypercapnia with or without acidemia in COVID-19 patients with severe acute respiratory failure may cause or exacerbate pulmonary vasoconstriction resulting in increased (even modest) RV afterload, RV-PA uncoupling and RVD with potential for reduced cardiovascular performance. 23 , 29 , 30 …”
Section: Pathophysiology Of Rv Dysfunction In Covid-19mentioning
confidence: 99%